Regulation of Flowering Time by Environmental Factors in Plants - Zion Lee; Sohyun Kim; Su Jeong Choi; Eui Joung; Moonhyuk Kwon; Hee Jin Park; Jae Sung Shim (Plants, 2023)
The timing of floral transition is determined by both endogenous molecular pathways and external environmental conditions. Among these environmental conditions, photoperiod acts as a cue to regulate the timing of flowering in response to seasonal changes. Additionally, it has become clear that various environmental factors also control the timing of floral transition. Environmental factor acts as either a positive or negative signal to modulate the timing of flowering, thereby establishing the optimal flowering time to maximize the reproductive success of plants. This review aims to summarize the effects of environmental factors such as photoperiod, light intensity, temperature changes, vernalization, drought, and salinity on the regulation of flowering time in plants, as well as to further explain the molecular mechanisms that link environmental factors to the internal flowering time regulation pathway.